OP16 Challenges experienced by community-based clinical nurse specialists in supporting the delivery of integrated diabetes care: a qualitative study. (2nd September 2017) - Riordan, F; McHugh, SM; Kearney, PM
Abstract : Background: In Ireland, more Diabetes Nurse Specialists (DNSs) have been introduced into the community as part of a national programme to standardise and improve diabetes care. DNSs support the delivery of a new model of care whereby uncomplicated type 2 diabetes (T2DM) is managed in primary care, and complicated T2DM is managed between primary and secondary care. Historically diabetes care in Ireland has often been delivered in an unstructured way, lacking integration between primary and secondary care. Given this context we wanted to understand the challenges faced by community-based DNSs in delivering a standardised service. Methods: We purposively sampled DNSs from community-based respondents to a national survey (n=25) according to four administrative regions of the national health service. We conducted focus groups and interviews using a semi-structured topic guide. Interviews were digitally recorded and transcribed into NVivo V.11 software for coding and analysis. Data analysis is on-going using thematic analysis. Results: Sixteen DNSs participated in 2 focus groups, and 8 interviews. Preliminary analysis suggested elements of the role presented a challenge. As DNSs require their Collaborative Practice Agreement to be signed off by each GP using their service, they were currently unable to prescribe in the community. Despite describing this as 'frustrating', DNSs suggested that prescribing could remove opportunities for relationship-building with GPs through discussion of medications. In the community, DNSs lacked the safety net of the hospital team to check things with, and had to work more autonomously, described as 'daunting'. Role understanding by other staff was another challenge; DNSs felt managers did not understand how the community role should work, which created difficulty when negotiating aspects of the role, including flexible working hours. The lack of a shared record between settings meant patient information from hospital appointments was not readily accessible by DNSs at GP practices and vice versa. This made patient follow-up and case discussion difficult when DNSs were off-site. The absence of administrative support in the role, considered 'crucial', was also highlighted. Further interviews with community DNSs are ongoing. Conclusion: Community-based DNSs faced challenges presented by aspects of their role, their relationship with other staff, their work environment, and the available organisational infrastructure and resources. Although recent policy reforms in Ireland have focused on improving the integrated management of diabetes in the community, findings from this study suggest DNSs may need to be better supported to ensure delivery of a standardised model of diabetes care.